Growth Response of Cocoa Seedlings (Theobroma cacao L.) to the Addition of Boiler Ash and Urea Fertilizer in Planting Media - Sri Nurmayanti; Ovy Erfandari; Andryande Reshi Gusta; Friko Pradana (CIB Nusantara, 2025)
The fertility of planting media can be improved or increased by inorganic or organic fertilization. One of them is by utilizing boiler ash, which is one type of solid waste by-product of palm oil processing plants. The objectives of this study were to evaluate the effect of boiler ash application on the growth of cocoa seedlings in nursery media, to assess the effect of urea fertilizer application on seedling growth, and to examine the potential interaction between boiler ash and urea fertilizer in improving the overall performance of cocoa seedlings. The research was conducted in the plantation of Lampung State Polytechnic in September 2022-January 2023, using a factorial randomized block design with two factors. The first factor was the dose of boiler ash (0, 150, 300, and 450 g. polybag-1) and the second factor was the dose of urea fertilizer (0, 3, and 6 g. polybag-1). The parameters observed were plant height, stem diameter, number of leaves, dry weight of stalks, and dry weight of roots. The application of boiler ash had a significant effect on the number of leaves parameter. The application of urea fertilizer significantly affects the parameters of plant height, stem diameter, number of leaves, and dry weight of stover. There was no interaction between boiler ash and urea fertilizer on all observation variables. The best result from the interaction of boiler ash and urea fertilizer was obtained in the treatment of 300 g.polibag-1 boiler ash and 3 g.polibag-1 urea fertilizer.